2009
DOI: 10.1038/nmeth.1301
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of haplotypes from single DNA molecules

Abstract: Determining the long-range haplotypes in a diploid individual is a major technical challenge. Here we report a method of molecular haplotyping by directly imaging multiple polymorphic sites on individual human DNA molecules simultaneously. We demonstrate the utility of this technology by accurately determining the haplotypes consisting of up to 16 single-nucleotide polymorphisms in genomic regions up to 50 kilobases.The recent successful completion of the HapMap project 1 and the availability of low-cost, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Ultimately, experimental approaches remain the most attractive solutions to the phasing problem. Current approaches include using emulsion PCR to condense polymorphic sites from a single template (7,8), genotyping from diluted aliquots of DNA fragments (9), allele-specific imaging of long-range PCR products (10), using long-range polony (11), genotyping from sperms (12), and isolating single chromosomes by interspecific cell fusion (13). Most of these methods were designed for haplotyping only a small number of markers.…”
mentioning
confidence: 99%
“…Ultimately, experimental approaches remain the most attractive solutions to the phasing problem. Current approaches include using emulsion PCR to condense polymorphic sites from a single template (7,8), genotyping from diluted aliquots of DNA fragments (9), allele-specific imaging of long-range PCR products (10), using long-range polony (11), genotyping from sperms (12), and isolating single chromosomes by interspecific cell fusion (13). Most of these methods were designed for haplotyping only a small number of markers.…”
mentioning
confidence: 99%
“…DNA barcoding methodologies are a promising alternative that may one day allow high-throughput detection of balanced structural differences; these methods include scanning fluorescently nick-labelled DNA molecules in nano-channel flow cells 51 or nanoslits 52 and the use of SNP-specific labelling of stretched DNA for haplotype resolution 53 . Similarly, absolute copy-number estimations made by amplifying single molecules using emulsion picolitre droplet PCR 54 or single-molecule sequencing of human genomes 55 offer tremendous potential to understand structural changes at the cellular level.…”
Section: Single-molecule Analysismentioning
confidence: 99%
“…Among mainstream haplotyping approaches621222627, imaging-based three methods are highly attractive, as their direct reading feature complements NGS in rapid assembly of short-reads of several hundred base pairs and provides feasibility and effectiveness in targeted genomic region studies. Several elegant studies have demonstrated the effectiveness of fluorescence imaging in haplotyping2829. Nevertheless, the diffraction limit of 200–300 nm restricted the resolution to be of ∼1,000 bp.…”
mentioning
confidence: 99%